Microphthalmia‐associated transcription factor/T‐box factor‐2 axis acts through Cyclin D1 to regulate melanocyte proliferation. (21st October 2015) - Pan, L.; Ma, X.; Wen, B.; Su, Z.; Zheng, X.; Liu, Y.; Li, H.; Chen, Y.; Wang, J.; Lu, F.; Qu, J.; Hou, L.
Abstract: Objectives: Control of cell proliferation is critical for accurate cell differentiation and tissue formation, during development and regeneration. Here, we have analysed the role of microphthalmia‐associated transcription factor MITF and its direct target, T‐box factor TBX2, in regulating proliferation of mammalian neural crest‐derived melanocytes. Materials and methods: Immunohistochemistry was used to examine spatial and temporal expression of TBX2 in melanocytes in vivo . RNAi and cell proliferation analysis were used to investigate functional roles of TBX2. Furthermore, quantitative RT‐PCR, western blot analysis and flow cytometry were used to further scrutinize molecular mechanisms underlying TBX2‐dependent cell proliferation. Results: TBX2 was found to be co‐expressed with MITF in melanocytes of mouse hair follicles. Specific Tbx2 knockdown in primary neural crest cells led to inhibition MITF‐positive melanoblast proliferation. Tbx2 knockdown in melan‐a cells led to reduction in Cyclin D1 expression and G1‐phase cell cycle arrest. TBX2 directly activated Ccnd1 transcription by binding to a specific sequence in the Ccnd1 promoter, and the defect in cell proliferation could be rescued partially by overexpression of Cyclin D1 in Tbx2 knockdown melanocytes. Conclusions: Results suggest that the Mitf‐Tbx2‐Cyclin D1 pathway played an important role in regulation of melanocyte proliferation, and provided novel insights into the complex physiology of melanocytes.